Nexus between green investment and technological innovation in BRI nations: What is the role of environmental sustainability and domestic investment? - Xiao, Zhuopeng; Qamruzzaman, Md. (Frontiers in Environmental Science, 2022)
The critical role of technological innovation has been extensively investigated by considering various aspects of macro-fundamentals across the world. Although the determents of technological innovation have been investigated predominantly from the perspective of firms, the role of macro-fundamentals is yet to be extensively explored. The aim of the study is to investigate the effects of green investment, measured by renewable energy; domestic investment measured by gross capital formation; and environmental sustainability measured by carbon emission on technological innovation in BRI nations for the period 2000–2021. The study used a cross-sectional dependency test, a unit root test following CADF and CIPS, an error correction-based panel cointegration test, ARDL, CS-ARDL, and a nonlinear ARDL. Furthermore, the directional causalities were documented by performing the heterogeneous causality test. Taking into account the findings of the study, it is revealed that green investment and domestic investment are positively connected with technological innovation in BRI nations, while environmental sustainability is correlated negatively and statistically significant to technological innovation. Furthermore, the asymmetric investigation established asymmetric effects from green investment, environmental sustainability, and domestic investment to technological innovation. According to the asymmetric coefficients, the positive and negative shocks of green and domestic investment disclosed positive and statistically significant links with technological innovation, whereas the asymmetric shocks in environmental sustainability revealed adverse ties to technological innovation in BRI nations. The study documented the unidirectional causal effects from green investment to technological innovation [GI→TI] and technological innovation to environmental sustainability [TI→ES]. Furthermore, the study documented bidirectional casualties between domestic investment, foreign direct investment, financial development, and technological innovation [TI←→DI; TI←→FDI; TI←→FD]. The study suggested that domestic capital formation and environmental protection in BRI nations should be actively promoted to accelerate technological innovation. Furthermore, the study postulated that investment in research and development should be encouraged with incentives for technological innovation.